SaudeBR-QA: A Question-Answering Corpus for the Health Domain in Brazilian Portuguese - Barros, Carlos Henrique S.; de Sousa, Gustavo F. Rodrigues; de Sousa, Rogério F. (Proceedings of the Regional School on Computing of Ceará, Maranhão, and Piauí (ERCEMAPI), 2025)
This paper presents SaudeBR-QA, a large-scale corpus composed of 23,382 question–answer pairs from the Brazilian Portuguese healthcare domain. The dataset was collected from a public health portal and contains real patient questions and verified answers from healthcare professionals. Each pair includes rich metadata such as medical specialty, quality metrics (scores from 0 to 5), and user likes. The corpus addresses the lack of domain-specific NLP resources for Brazilian Portuguese. SaudeBR-QA is expected to support research in text classification, automatic answer quality prediction, and other health-related text mining tasks.